Coupled thermo-electro-mechanical models for thermal ablation of biological tissues and heat relaxation time effects. (13th December 2019) - Singh, Sundeep; Melnik, Roderick
Abstract: Thermal ablation is a widely applied electrosurgical process in medical treatment of soft biological tissues. Numerical modeling and simulations play an important role in prediction of temperature distribution and damage volume during the treatment planning stage of associated therapies. In this contribution we report a coupled thermo-electro-mechanical model, accounting for heat relaxation time, for more accurate and precise prediction of the temperature distribution, tissue deformation and damage volume during the thermal ablation of biological tissues. Finite element solutions are obtained for most widely used percutaneous thermal ablative techniques, viz., radiofrequency ablation (RFA) and microwave ablation (MWA). Importantly, both tissue expansion and shrinkage have been considered for modeling the tissue deformation in the coupled model of high temperature thermal ablation. The coupled model takes into account the non-Fourier effects, considering both single-phase-lag (SPL) and dual-phase-lag (DPL) models of bio-heat transfer. The temperature-dependent electrical and thermal parameters, damage-dependent blood perfusion rate and phase change effect accounting for tissue vaporization have been accounted for obtaining more clinically relevant model. The proposed model predictions are found to be in good agreement against the temperature distribution and damage volume reported by previous experimental studies. The numerical simulation results revealed that the non-Fourier effects cause a decrease in the predicted temperature distribution, tissue deformation and damage volume during the high temperature thermal ablative procedures. Furthermore, the effects of different magnitudes of phase lags of the heat flux and temperature gradient on the predicted treatment outcomes of the considered thermal ablative modalities are also quantified and discussed in detail.